Hemangiomatosis of the spleen in a patient with Klippel-Trenaunay syndrome: A case report - Dhaneshwar Namdeorao Lanjewar; Kinalee Prafullbhai Chothani; Mitsu Vinay Vaishnav; Gyaneshwar Rao (Indian Journal of Pathology and Microbiology)
Hemangiomatosis of the spleen is a benign vascular condition occurring as a manifestation of systemic angiomatosis. It is usually associated with Klippel-Trenaunay syndrome (KTS), which is a rare congenital malformation characterized by a triad of varicose veins, bony and soft tissue hypertrophy, and cutaneous and visceral hemangiomas and/or venous malformations. The association of splenic hemangiomatosis with KTS is less documented in the literature. In this report, we describe a 63-year-old female who presented with massive splenomegaly, the histopathology of which showed features of diffuse hemangiomatosis. Based on the histopathological diagnosis, a retrospective evaluation of the patient was carried out and she was diagnosed as KTS. To the best of our knowledge, this is the first report in the Indian literature describing splenic hemangiomatosis in a patient with KTS.